Body of Writing : Figuring Desire in Spanish American Literature - Prieto, Rene (Book collections on Project MUSE., 2000)
A psychoanalytic exploration through a series of reading of Latin American fiction of Roland Barthes' contention that literary texts have human form and are always an anagram of our erotic body.